Attack strategies in birds of prey - Brighton, C (2016)
Pursuit behaviours are vital in predator-prey interactions and in courtship for many flying animals. Existing research on target-directed flight behaviours in insects[1-9], birds[10-12] and bats[13] has aimed at identifying simple geometric rules describing the pursuit-flight trajectories. However, these geometric rules are only part of the picture as they only consider the outcome of the commanded changes in flight kinematics, and not the underlying guidance laws (dynamics) which generate these commands. To intercept a target, a pursuer implements a guidance law using sensory feedback to determine the required change in flight velocity, and the resulting kinematics determines the flight geometry. Most of the research until recently has examined insect flight systems, as the ethics of working with birds of prey are more complex and measuring their wide-ranging flight trajectories is difficult. Studies of predator-prey pursuit in birds have only described the geometrical rules for target interception, therefore overlooking the guidance laws which implement them. Therefore the aim of this thesis is to complete the picture by identifying the guidance laws used by birds of prey as they pursue and intercept targets both in the air and on the ground. I used onboard cameras and GPS to study attack flights in peregrine falcons (Falco peregrinus), and high-speed ground photogrammetry for attacks in Harris' hawks (Parabuteo unicinctus), to show that two different raptor species effectively implement the same guidance law of pure proportional navigation for intercepting manouevring and non-manouevring prey-targets. Proportional navigation is a feedback law whereby the bird’s line-of-sight rate is fed back, in order to command a turn-rate in proportion to the change in line-of-sight rate, with a constant of proportionality N. Harris’ hawks were found to use this guidance law in its simplest case with an N of approximately 1. This amounts to a pure pursuit course, meaning the bird maintains a heading angle of zero at all times (its velocity vector points at the target). Peregrine falcons were found to use a variety of values of N resulting in a quicker path to interception. A remarkable feature of most bird of prey eyes is that they possess two regions of high visual acuity - the shallow and deep foveae. The deep fovea is optimised for long-range vision, and is directed at approximately 45° to the side of the head. It has been proposed that the head is held in line with the body for streamlining, while the body is turned in flight to fixate the image of the prey on the deep fovea, resulting in a curved trajectory. My results contradict this theory, as falcons were seen to use saccadic head movements to maintain the image of the prey in their field of view whilst flying along curved trajectories - suggesting a different visual strategy. I provide the first quantitative analysis of how birds are able to guide their flight for successful prey capture. Not only does this provide new insights into animal behaviour and evolution, but this research has many applications in engineering, where there is a wide and growing interest in vision-based approaches to guidance and control in both civil and military spheres.